Positive solution of singular fractional differential system with nonlocal boundary conditions - Wu, J.; Zhang, Xinguang; Liu, L.; Wu, Yong Hong (SpringerOpen, 2014)
In this paper, we consider the existence of positive solutions for a singular fractionaldifferential system involving a nonlocal boundary condition which is given by a linearfunctional on C[0, 1] with a signed measure. By looking for the upper and lowersolutions of the system, the sufficient condition of the existence of positive solutionsis established; some further cases are discussed. This is proved in the case of strongsingularity and with a signed measure.